Advances in the biology and treatment of pediatric central nervous system tumors. Issue 1 (February 2016) - Vitanza, Nicholas A.; Cho, Yoon-Jae
Abstract : Purpose of review: Central nervous system tumors represent the most common solid tumors in children and are a leading cause of cancer-related fatalities in this age group. Here, we provide an update on insights gained through molecular profiling of the most common malignant childhood brain tumors. Recent findings: Genomic profiling studies of medulloblastoma, ependymoma, and diffuse intrinsic pontine glioma (diffuse midline glioma, with H3-K27M mutation), have refined, if not redefined, the diagnostic classification and therapeutic stratification of patients with these tumors. They detail the substantial genetic heterogeneity across each disease type and, importantly, link genotypic information to clinical course. The most aggressive, treatment-resistant (and also treatment-sensitive) forms within each disease entity are identified, and their potentially actionable targets. Summary: Molecularly based classification of pediatric brain tumors provides a critical framework for the more precise stratification and treatment of children with brain tumors.